CURRENT STATE AND PROBLEMS OF MODERNIZATION OF ECOLOGICAL FRAMEWORK OF REGIONS OF THE STEPPE ZONE OF EUROPEAN RUSSIA - A. A. Chibilyov (jr.) (Ûg Rossii: Èkologiâ, Razvitie, 2019)
Aim. The aim of the study is to assess the current state of the elements of the naturalecological framework of the steppe regions of European Russia and the peculiarities of its spatial distribution.Discussion. The most important component of the environmental framework of the steppe regions of European Russia is the system of relatively large zonal landscape areas of the nature reserve fund which contribute to the preservation of biodiversity, the functional integrity of landscapes and the development of ecological networks. As of January 1, 2018, the natural reserve fund of the federal level in the territory of the considered mezoregion is represented by 22 specially protected natural territories (10 reserves, 5 national parks and 7 wildlife sanctuaries) with a total area of 16.1 thousand km2. The share of the area of specially protected natural reservation is about 2% of the area of the considered mezoregion. Practically for all the regions under consideration, there is a situation where numerous natural territories with “prospective” status are considered for integration into the nature reserve fund; however, the efforts of the scientific community, environmental services and relevant ministries are not very active in implementing projects to give them corresponding status.Conclusion. For the territory stretching from the northern border of the Saratov region to the central part of the Krasnodar Territory, the problem of the absence of cores and key elements constituting the framework of the nature reserve fund is most acute. In six territorial subjects of the Mesoregion, there are no specially protected natural steppe reservations of the federal level. The analysis of modern territorial planning schemes of the steppe regions indicates that the environmental framework of European Russia has not yet become the basis for the adoption of urban planning decisions. At the same time, its structural elements (preserved zonal landscapes, natural and derived landscape complexes), along with autonomously functioning nature-like territorial complexes, will help create a favorable environment for the population.